The Relationship between Knowledge of Balanced Nutrition and the Nutritional Status of Female Adolescents at SMA N 1 Moyo Utara, Sumbawa Regency - Fitri Setianingsih; Luh Putu Sriyuliastuti; Galuh Permatasari; Ana Lestari; Nurlaila Agustikawati (International Journal Of Health Science, 2025)
The nutritional health status of adolescent girls is a picture of the physical well-being of women due to the fulfillment of nutritional needs in the body. Adolescent nutrition can affect reproductive health to prepare for reproduction from preconception, pregnancy, childbirth and postpartum. Stunting prevention efforts can be done by optimizing nutrition & child health from pregnancy to the age of 2 years. Therefore, the readiness of adolescent girls to undergo the pregnancy process later so as not to give birth to stunted children needs to be questioned. The knowledge of adolescent girls is very influential in the action of preparing for pregnancy in order to prevent stunting. To avoid the occurrence of KEK and BMI underweight category, it is expected that adolescent girls prepare themselves by fulfilling nutritional needs in the body. Thus, adolescent girls must understand and pay attention to the daily food intake consumed that contains nutrients so that nutritional needs in the body can be met. The purpose of this study was to determine the analysis of the relationship between knowledge of balanced nutrition and the nutritional status of adolescent girls at SMA N 1 Moyo Utara. This type of research is quantitative research with a cross-sectional design. The population in this study were adolescent girls at SMA N 1 Moyo Utara. The sampling technique was Accidental sampling. The results of the study showed that the knowledge of female adolescents about balanced nutrition was mostly sufficient, as many as 63 (63.6%) respondents. The nutritional status of female adolescents at SMA N 1 Moyo Utara, Sumbawa Regency was mostly thin, as many as 51 (51.5%). The results of the Fisher Exact test showed a p value of 0.044, meaning Ho was rejected and Ha was accepted, which means there is a relationship between knowledge about balanced nutrition and nutritional status in female adolescents at SMA N 1 Moyo Utara, Sumbawa Regency.